Variable spaced particle in mesh‐free method to handle wave‐floating body interactions. (26th June 2019) - Rijas, A.S.; Sriram, V.; Yan, S.
Summary: In this work, the motion of a two‐dimensional rectangular freely floating body under waves is simulated using Improved Meshless Local Petrov‐Galerkin method with Rankine Source function (IMLPG_R) with variable spacing resolutions. The IMLPG_R method is a particle method that solves Navier–Stokes equations using the fractional step method to capture the wave properties. However, many existing particle methods are computationally intensive to model the wave‐floating body due to the requirement of fine particles, needing uniform distribution throughout the domain. To improve the computational efficiency and capture the body response properly, variable spaced particle distribution with fine resolution near the floating body and coarse resolution far from the body is implemented. Numerical schemes to handle variable resolutions are reported. An iterative scheme to handle the wave‐floating body is implemented in the particle method. Two test cases, one with small wave and another with steep waves, are simulated for uniform particle distribution and the result shows good agreement with literature. Based on this, the performance of the variable spaced particle distribution is tested in coupling with floating body solver. The application of the method for wave impact load from the green water loading of the floating structure is also simulated. Abstract : Particle methods are computationally intensive to model the wave‐floating body due to the requirement of fine particles near the body, needing uniform distribution throughout the domain. To improve the computational efficiency and capture the body response properly, variable spaced particle distribution with fine resolution near the floating body and coarse resolution far from the body is implemented and 90% reduction in computation time with respect to uniform particle distribution is achieved by using the proposed novel approach. A higher‐order prediction correction scheme is implemented to model the wave‐floating body motions in mesh‐free scheme.